CLINICAL SUPERVISION: A CONTRIBUTION TO IMPROVING QUALITY INDICATORS IN NURSING CARE - Sérgio, Mafalda Sofia Santos Brás Baptista; Carvalho, António Luís Rodrigues Faria de; Pinto, Cristina Maria Correia Barroso (Cogitare Enfermagem, 2023)
Objective: to compare indices and indicators of the quality of nursing care in inpatient, medical and surgical services when clinical supervision is implemented. Method: an observational, retrospective study with a quantitative approach and simple random sampling of audit records related to the quality of nursing care (n=719). The research took place between August 2020 and August 2022, in two private hospitals in the Lisbon region, Portugal, where audits related to the quality of nursing care were carried out, and clinical supervision was implemented in one of the hospitals. Descriptive and inferential statistics were used. Results: analysis of the records when comparing the hospitals and services showed an increase in the desired and adequate quality scores (≤5 and ≤4) in the services of the hospital where clinical supervision was implemented. Conclusion: Clinical supervision allows teams to be strategically monitored in the practice of care, increasing quality indices and indicators with a direct impact on the patient.